Cooperation with Police in China: Surveillance Cameras, Neighborhood Efficacy and Policing. (7th December 2020) - Wu, Yuning; Sun, Ivan Y.; Hu, Rong
Abstract : Objective: Given the paucity of research on Chinese cooperation with the police and the underdevelopment of knowledge on the influence of surveillance videos on such cooperation, this study investigates the interplay of surveillance cameras and neighborhood collective efficacy, police fairness, and police effectiveness in shaping public willingness to cooperate with the police. Methods: Relying on face‐to‐face survey interview data collected from 751 residents in a southern city in China, this study used Ordinary Least Squares (OLS) regression analysis to examine the key correlates of Chinese willingness to cooperate with the police. Results: The results reveal positive influences of video surveillance, collective efficacy, police fairness, and police effectiveness on cooperative desires. Notably, the cooperation‐promoting effect of surveillance cameras is most profound among people who live in neighborhoods with high levels of collective efficacy and people who perceive low levels of police fairness. Conclusion: These findings affirm that formal and informal social control interlock in determining the public's cooperative willingness, and reiterate the need for testing theoretical interactions. They also help us understand the underlying reasons that may explain the public's reliance on video surveillance to make their decisions about helping the police in the context of China.